Ultralow Pt Catalyst for Formaldehyde Removal: The Determinant Role of Support - Wang, Qiyan; Zhang, Chunlei; Shi, Lei; Zeng, Gaofeng; Zhang, Hui; Li, Shenggang; Wu, Ping; Zhang, Yelei; Fan, Yiqiu; Liu, Guojuan; Jiang, Zheng; Liu, Zhi; et al. (iScience, 2018)
Supported Pt catalyst has been intensively investigated for formaldehyde elimination owing to its superior reactivity at room temperature (RT). However, the high Pt content is challenging because of its high cost. Herein, we report PbO-supported Pt catalysts with only 0.1 wt % Pt, which can achieve complete conversion of formaldehyde and reliable stability at RT under demanding conditions. Both experiments and simulations demonstrate that PbO interacts strongly with the Pt species, resulting in tight Pb-O-Pt bonding at the metal/support interface and concomitant activation of the surface lattice oxygen of the support. Moreover, PbO exhibits an extremely high capacity of formaldehyde capture through methylene glycol chemisorption rather than the common hydroxyl-associated adsorption, presenting a different reaction mechanism because the active surface lattice oxygen in the vicinity of Pt species offers improved reactivity. This work provides a valuable example for the design of an efficient catalyst for formaldehyde and potentially oxidation of other carbohydrates.